Desarrollo de equipos de alto rendimiento en la gerencia del talento humano (2018)
Implementing all the knowledge to make high performance groups inside the companies, we will see the benefits in a short time lapse like: high performance,increment in the productivity and a better work environment, making more investment in the business sector. The principal characteristic of this teams we can see that the leader is who makes the strategies possibles to develop the high performance groups, without forget the leader must have personal qualities to get the success.